Parent and caregiver perceptions about the safety and effectiveness of foreign and domestic vaccines in Shanghai, China. - Zhuoying Huang; Xiaodong Sun; Abram L Wagner; Jia Ren; Matthew L Boulton; Lisa A Prosser; Brian J Zikmund-Fisher (PLoS ONE, 2018)
BACKGROUND:Chinese parents have access to domestic and foreign vaccines for their children. Their vaccine preferences are unclear, especially given recent pharmaceutical quality scandals and widely held beliefs deriving from Traditional Chinese Medicine (TCM). This study characterized parental beliefs about the safety and effectiveness of Chinese and foreign vaccines. METHODS:In May 2014, caregivers of young children at public immunization clinics in Shanghai, China, responded to a survey on vaccine perceptions. The two outcomes (differential belief in the effectiveness and safety of foreign vs domestic vaccines) were separately regressed onto demographic predictors in multinomial logistic regression models. RESULTS:Among 618 caregivers, 56% thought the effectiveness of domestic and foreign vaccines were comparable; 33% thought domestic were more effective and 11% foreign. Two-thirds thought foreign and domestic vaccines had similar safety; 11% thought domestic were safer and 21% thought foreign were safer. Compared to college graduates, those with a high school education or less had greater odds of believing domestic vaccines were more effective, and also had greater odds of believing imported vaccines were safer. Greater trust in TCM was not associated with differential beliefs in the effectiveness or safety of domestic vs foreign vaccines. CONCLUSIONS:Although there is no evidence that foreign and domestic vaccines differ in either effectiveness or safety, less educated caregivers in China (but not those with greater trust in TCM) appear to believe such differences exist. Further exploration of the causes of these beliefs may be necessary in order to optimize vaccine communications in China.